Foods, Nutrients and Food Ingredients with Authorised EU Health Claims. Volume 2 - Sadler, M. J. (Woodhead Publishing, 2015)
The second volume of Foods, nutrients and food ingredients with authorised EU health claims continues from Volume 1, which provided a comprehensive overview of many of the permitted health claims for foods and nutrients approved under European Regulation EC 1924/2006. This new volume discusses more of the health claims authorised to date for use in the EU. The chapters cover details of various permitted claims, such as the approved wording, conditions of use, the target group for the claims, the evidence for the claimed health benefits, and where appropriate details of other relevant legislation, consumer-related issues and future trends. The book opens with an overview of regulatory developments relating to health claims. Part One reviews authorised disease risk reduction claims and proprietary claims. The second part investigates ingredients with permitted 'general function' claims, with chapters examining ingredients such as red yeast rice, glucomannan and guar gum. The final section of the book explores foods and nutrients with permitted health claims, including chapters on authorised EU health claims for prunes, foods with low or reduced sodium or saturated fatty acids, and claims for essential and long chain polyunsaturated fatty acids.
Keywords: Functional foods -- European Union countries.; Nutrition -- European Union countries.; Diet therapy -- European Union countries.; elektronické knihy; electronic books